Extreme flood events and riparian vegetation: current knowledge and research gaps across mountain and temperate rivers with emphasis on the Alps - Gianmarco Tavilla; Camilla Wellstein (Alpine Botany, 2026)
Despite their critical role in shaping Alpine and non-Alpine ecosystems, the specific impacts of extreme flood events on riparian vegetation remain poorly understood. In Alpine habitats, such events induce rapid channel reworking, entailing abrupt sediment redistribution and changes in channel width, which trigger immediate vegetation responses. This review employed distinct search syntaxes across Scopus, Web of Science (WoS), and Google Scholar databases to identify relevant papers on this topic. Through a systematic screening of 1,948 records, complemented by citation searching, we identified 22 studies in which the response of riparian vegetation to high-magnitude or flash-flood events was the primary focus. Only a few of these concerned the European Alps, so the synthesis also draws on transferable evidence from comparable mountain and temperate rivers. Analysis of these datasets reveals that geomorphology and hydrology predominate, while studies focusing on riparian vegetation remain scarce. Studies report that flash events often remove pioneer and herbaceous cover while areas with dense woody vegetation (e.g., willows and poplars) exhibit some resistance against erosion. Alpine systems are marked by steep gradients and snowmelt-driven floods. They show both high biodiversity and shifts in species composition, as post-flood recovery progresses from early-successional, flood-tolerant species toward native shrubs and trees. In fact, the typical habitats of such environments are listed in the Annex I of the EU Habitat Directive. Many studies cite the value of integrating remote sensing with field validation, yet they also note gaps in long-term, multi-site assessments of sediment, large wood transport, and species-specific recovery trajectories in Alpine riparian zones. This review highlights a lack of studies employing a phytosociological approach to track post-flood successional trajectories in Alpine plant communities, thereby providing a foundational step towards comprehensively addressing the ecological effects of flash floods in riparian zones.